Estimation of overdiagnosis using short-term trends and lead time estimates uncontaminated by overdiagnosed cases: Results from the Norwegian Breast Screening Programme. (December 2016) - Michalopoulos, Dimitrios; Duffy, Stephen W
Background: Estimating overdiagnosis in cancer screening is complicated. Using observational data, estimation of the expected incidence in the screening period and taking account of lead time are two major problems. Methods: Using data from the Cancer Registry of Norway and the Norwegian Breast Cancer Screening Programme, we estimated incidence trends, using age-specific trends by year in the pre-screening period (1985–95). We also estimated sojourn time and sensitivity using interval cancers only. Thus, lead time estimates were uncontaminated by overdiagnosed cases. Finally, we derived estimates of overdiagnosis separately for all cancers, and for invasive cancers only, correcting for lead time, using two different methods. Results: Our results indicate that overdiagnosis of all cancers, invasive and in situ, constituted 15–17% of all screen-detected cancers in 1996–2009. For invasive cancers only, the corresponding figures were -2 to 7% in the same period, suggesting that a substantial proportion of the overdiagnosis in the Norwegian Programme was due to ductal carcinoma in situ. Conclusion: Using short-term trends, instead of long, prior to screening was more effective in predicting incidence in the screening epoch. In addition, sojourn time estimation using symptomatic cancers only avoids over-correction for lead time and consequently underestimation of overdiagnosis. Longer follow-up will provide more precise estimates of overdiagnosis.